Naczynie z przedstawieniem antropomorficznym z nekropoli w Miłosławicach na Dolnym Śląsku - Lasak, Irena; Kaczmarek, Maciej (My University, 2012)
The paper discusses a vessel with a lid, the urn from one of the graves from the Lusatian culture cemetery in Miłosławice in Lower Silesia (Dolny Śląsk). It presents a stylistic analysis of images from the urn and its lid, as well as an attempt at their semantic interpretation, on the basis of former conclusions from the subject literature, regarding in particular anthropomorphic images on pottery dating from the Late Bronze and Early Iron Age.
Keywords: archeologia; epoka brązu; wczesna epoka żelaza; Dolny Śląsk; łużyckie pola popielnicowe; kultura łużycka; okres halsztacki; ceramika; cmentarzyska